2020
DOI: 10.1136/jitc-2019-000282
|View full text |Cite
|
Sign up to set email alerts
|

Potent STING activation stimulates immunogenic cell death to enhance antitumor immunity in neuroblastoma

Abstract: BackgroundNeuroblastoma (NB) is a childhood cancer for which new treatment options are needed. The success of immune checkpoint blockade in the treatment of adult solid tumors has prompted the exploration of immunotherapy in NB; however, clinical evidence indicates that the vast majority of NB patients do not respond to single-agent checkpoint inhibitors. This motivates a need for therapeutic strategies to increase NB tumor immunogenicity. The goal of this study was to evaluate a new immunotherapeutic strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 72 publications
1
104
0
Order By: Relevance
“…As STING induced both NFkB-and IFN-pathway activation, agonizing its activity may be an interesting strategy to upregulate these pathways to potentially induce MHC-I upregulation. This is further substantiated by the correlation between STING expression and HLA-associated genes in neuroblastoma [178]. In addition, preclinical studies have reported superior effects of CPI therapy in combination with STING agonists [179,180].…”
Section: Inducing Mhc-i Expression In Cancer Via Sting Inductionmentioning
confidence: 79%
“…As STING induced both NFkB-and IFN-pathway activation, agonizing its activity may be an interesting strategy to upregulate these pathways to potentially induce MHC-I upregulation. This is further substantiated by the correlation between STING expression and HLA-associated genes in neuroblastoma [178]. In addition, preclinical studies have reported superior effects of CPI therapy in combination with STING agonists [179,180].…”
Section: Inducing Mhc-i Expression In Cancer Via Sting Inductionmentioning
confidence: 79%
“…Advantages of DDS include their ability to profoundly alter and improve drug pharmacokinetics, provide targeted drug delivery, and therefore alleviate TRAEs whilst enhancing therapeutic outcomes [ 125 , 126 , 127 , 128 ]. The three main DDS discussed here are liposomes, polymers and hydrogels ( Table 3 ) [ 14 , 123 , 124 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. Liposomes are cationic lipid structures with an aqueous core, making them great candidates for encapsulating negatively charged, hydrophilic CDN compounds [ 138 , 139 , 140 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…They also significantly improved responses to anti-PD-1 and anti-CTLA-4 ICI, inhibited tumour growth, induced immunological memory, increased OS and could be systemically administered [ 14 ]. The same group used this technology to successfully enhance STING activation in neuroblastoma cells as well as within the TME and showed synergistic effects when administered with anti-PD-L1 ICI [ 132 ]. The Ting group used acetalated dextran (Ace-DEX) to develop polymeric microparticles for cGAMP loading using electrospray, resulting in >90% encapsulation of cGAMP into Ace-DEX microparticles [ 133 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Hence, cGAS-STING signaling plays a crucial role in the immune environment of different tumor microenvironments, including the lung cancer one. The STING activation has also been found beneficial in neuroblastoma via increasing the potent tumoricidal T cell-mediated immune response ( 159 ). The nanoparticle-based delivery of the STING activator has also increased the antitumor immune response (increased M2 to M1 macrophage polarization, IFN-γ producing T cells, tumor cell apoptosis, and CD4 + and CD8 + T cell infiltration in the tumor microenvironment) in the PD-L1-insensitive triple-negative breast cancer ( 160 ).…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%